DAYA SAING KOPI ARABIKA DI MASA PANDEMI - Soetriono Soetriono; Ariq Dewi Maharani; Dimas Bastara Zahrosa (Universitas Sebelas Maret, 2024)
During the COVID-19 pandemic, most of the export-oriented Arabica coffee plantations experienced production and productivity constraints due to decreased maintenance costs; besides, export opportunities were constrained by regulations issued by several countries requiring the product to be sterile from the COVID-19 virus. export. Based on the above phenomenon, this study aims to analyze the impact of the COVID-19 pandemic on Arabica coffee agribusiness, especially the profitability and competitiveness of Arabica coffee during the pandemic. The method used to select the area is the production center area around Mount Ijen, the Ijen Ring Region. The research is descriptive, combined research (mixed methods), and the method of collecting data uses primary and secondary data, as well as purposive sampling and incidental sampling with observation and interviews. The analysis tool uses competitiveness and policy with PAM (Policy Analysis Matrix). Arabica coffee during the pandemic is still profitable both financially (privately) and economically (socially), has great competitiveness and export opportunities, and is indicated to be able to compete with similar commodities, both imported and domestic products.